The Healing Potential of Ficus virens: A Pharmacognostical and Phytochemical Perspective on the White Fig - Pal, Akriti; Gupta, Pooja; Fatima, Zoya; Patel, Nitin Kant (Journal of Neonatal Surgery, 2025)
Ficus virens Aiton, widely recognized as the White Fig or Pilkhan, is a versatile arboreal species within the Moraceae family, esteemed in various traditional healing systems including Ayurveda and Siddha. Historically utilized for its therapeutic efficacy, the species has been employed in the management of pathophysiological conditions such as gastrointestinal dysfunctions, respiratory ailments, dermatopathies, and chronic inflammatory disorders. These pharmacological effects are largely attributed to its extensive repertoire of bioactive secondary metabolites, notably flavonoids, triterpenoids, tannins, alkaloids, phenolic acids, and saponins. This review offers a comprehensive, interdisciplinary analysis of F. virens through a pharmacognostical and phytochemical lens, encompassing its macro- and micromorphological traits, anatomical diagnostics, powder microscopy, and organoleptic characteristics. Furthermore, this synthesis critically appraises experimental evidence from in vitro and in vivo models that substantiate its diverse pharmacodynamic actions, including antioxidant, antimicrobial, hepatoprotective, antidiabetic, wound-healing, and neuroprotective activities. The paper also outlines its emerging utility in pharmaceutical formulations, nutraceutical innovations, and cosmeceutical applications. Despite the growing scientific interest, the pharmacological advancement of F. virens is constrained by significant research lacunae—particularly the lack of randomized clinical trials, insufficient mechanistic elucidation, and variability in phytochemical standardization. Future perspectives underscore the necessity of integrating cutting-edge technologies such as metabolomics, high-throughput screening, nanotechnology-based delivery systems, and green extraction protocols. Concurrently, ensuring sustainable harvesting and establishing rigorous quality control standards are essential for its translational success. Overall, Ficus virens emerges as a pharmacobotanical candidate of significant clinical and industrial promise within evidence-based herbal medicine